AKTIVITAS BIOINSEKTISIDA EKSTRAK DAUN MAJA (Crencentia cujete Linn.) TERHADAP Rhipicephalus sanguineus DARI ANJING LOKAL - Roman, Bela Krista; Laut, Meity Marviana; Almet, Julianty (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2021)
Brown tick, Rhicephalus sanguineus generally known as a very adaptive tick, is widely spread on tropical, subtropical, and temperate regions, and infested dogs living on not only rural but urban areas. Synthetic acaricides are the most widely control measures. However, with the development of tick resistance, plant-derived components are highly investigated. The present study aims to investigate the activity of Crecentia cujete Linn. leaves extract on R. sanguineus. Fifty adult R. sanguineus were collected from local dogs and used in this study. Ticks are divided into the control and treatment groups. Aquadest and deltamethrin were sprayed to ticks in the negative and positive control groups, respectively. The three treatment groups were given maja leaves extract of 2.5%, 5%, and 10%. The tick mortality was observed for 12 hours of exposure to the extracts. All extracts exhibited similar lethal effects on R. sanguineus with total mortality (100%) after 4 hours exposure, compared to the standard therapy. The highest extract concentration (10%) reduces ticks faster compare to other concentrations. Thus, this study suggests that strong acaricidal activity and mortality rate was dose-dependent. This finding needs further scientific investigation to prove.